RISK FACTORS OF CHRONIC KIDNEY DISEASE LEADING TO DIALYSIS IN PATIENTS PRESENTING AT AYUB TEACHING HOSPITAL ABBOTTABAD - Malik, Saqib; Syed, Zainab; Naz, Farhat; Rehman, Najma; Rauf, Abdul; Ali, Rashid (Journal of Ayub Medical College Abbottabad, 2019)
Background: There has been an immense increase in the incidence and prevalence of chronic kidney disease (CKD) in the last few years globally ultimately leading to chronic renal failure (CRF). Developing countries are more prone to suffer the complications due to greater poverty and higher expenses of treatment. Dialysis has become a routine procedure rather than exception. This study was conducted with the purpose to determine risk factors of CKD patients leading to dialysis. Methods: This cross-sectional study was conducted at Ayub Teaching Hospital, Abbottabad (ATH) from December 2018 to April 2019. Patients admitted at the dialysis unit of ATH with the diagnosis of CRF were included. Data was analysed using SPSS version 20.0. Results: Out of 152 CRF patients 99 (65.1%) were males. Majority of patient with CKD were on dialysis for more than 10 months. Out of 152 patients of CRF, 32 (21.1%) were diabetic. Hypertension was previously diagnosed in 148 (97.4.%). Conclusion: Hypertension was identified as major cause leading to CRF and subsequently dialysis. Keywords: Chronic Kidney Disease; Dialysis; Risk Factors